2021
DOI: 10.1021/acs.joc.1c02111
|View full text |Cite
|
Sign up to set email alerts
|

Visible-Light-Mediated Cross Dehydrogenative Coupling of Thiols with Aldehydes: Metal-Free Synthesis of Thioesters at Room Temperature

Abstract: Thioesters play a crucial role in biological systems and serve as important building blocks for organic synthesis. Herein, Eosin Y and TBHP mediated photochemical cross dehydrogenative coupling (PCDC) between feedstock aldehydes and thiols has been described at room temperature to synthesize thioesters. This thioesterification protocol proceeds smoothly to give the desired products in good to excellent yields by the suitable PCDC of both alkyl/aryl- aldehydes with a variety of alkyl/aryl-thiols and generates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 111 publications
0
13
0
Order By: Relevance
“…Furthermore, during mechanistic studies, it has been revealed that the generation of an acyl radical from an aldehyde was intercepted by a disulfide intermediate to afford the desired thioester. 83…”
Section: C–s Bond Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, during mechanistic studies, it has been revealed that the generation of an acyl radical from an aldehyde was intercepted by a disulfide intermediate to afford the desired thioester. 83…”
Section: C–s Bond Formationmentioning
confidence: 99%
“…Furthermore, during mechanistic studies, it has been revealed that the generation of an acyl radical from an aldehyde was intercepted by a disulfide intermediate to afford the desired thioester. 83 Recently, Khade et al have reported the practical synthesis of 1,3-dithiolanes (182). These scaffolds were obtained without using any base and external additives from terminal aromatic and heteroaromatic alkynes (151) via the photoinduced catalyst eosin Y.…”
Section: Thionationmentioning
confidence: 99%
“…The direct functionalization of sp 3 C−H bonds via radical chemistry constitutes an elegant platform for advanced organic synthesis [53] . Recently, α‐sp 3 C−H bonds of cyclic and acyclic ethers have been explored as synthetic handle for the incorporation of thioester functionality [54] .…”
Section: Thiocarbonylation Of Ethereal Sp3 C−h Bondsmentioning
confidence: 99%
“…Roy [59] described the synthesis of thioesters at room temperature by eosin Y and tert ‐butyl hydroperoxide (TBHP) mediated photochemical cross dehydrogenation coupling. Various alkyl/aryl aldehydes or alcohols could give desirable products with thiols and produced water and butanol as green by‐products (Scheme 27).…”
Section: Synthesis Of Thioesters From Aldehydesmentioning
confidence: 99%